Total Flavonoid Contents and the Expression of Flavonoid Biosynthetic Genes in Breadfruit (Artocarpus altilis) Scions Growing on Lakoocha (Artocarpus lakoocha) Rootstocks - Yuchan Zhou; Steven J. R. Underhill (Plants, 2023)
Breadfruit (Artocarpus altilis) is a traditional fruit tree of 15–30 m height in the tropics. The presence of size-controlling rootstock in the species is not known. A small tropical tree species, lakoocha (Artocarpus lakoocha), was recently identified as a potential vigor-controlling rootstock, conferring over a 65% reduction in breadfruit tree height. To better understand the intriguing scion/rootstock interactions involved in dwarfing, we investigate flavonoid accumulation and its regulation in breadfruit scions in response to different rootstocks. To this end, we isolated a chalcone synthase cDNA, AaCHS, and a full-length bifunctional dihydroflavonol 4-reductase cDNA, AaDFR, from breadfruit scion stems. The expression of both AaCHS and AaDFR genes was examined over the period of 16 to 24 months following grafting. During the development of the dwarf phenotype, breadfruit scion stems on lakoocha rootstocks display significant increases in total flavonoid content, and show upregulated AaCHS expression when compared with those on self-grafts and non-grafts. There is a strong, positive correlation between the transcript levels of AaCHS and total flavonoid content in scion stems. The transcript levels of AaDFR are not significantly different across scions on different rootstocks. This work provides insights into the significance of flavonoid biosynthesis in rootstock-induced breadfruit dwarfing.